Prevalence of group B streptococcus colonization in Iranian pregnant women: A systematic review and meta-analysis - Mohammad Hossein YektaKooshali; Masoud Hamidi; Seyed Mohammad Taghi Razavi Tousi; Iraj Nikokar (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Group B Streptococcus (GBS) is an important pathogen in newborns and pregnant women. Objective: The present study was carried out to estimate the prevalence of GBS colonization in pregnant women in Iran. Materials and Methods: This systematic review and meta-analysis was based on Preferred Reporting Items for Systematic Reviews and Meta-Analysis guideline using the national databases including Society for Information Display, Magiran, Irandoc,Iran Medex, and international databases including MEDLINE, Web of Science, Scopus,PubMed, Science-Direct, Cochrane, Embase, Elton Bryson Stephens Company, Centre for Evidence-Based Medicine, Cumulative Index to Nursing and Allied Health Literature, and Google Scholar, published by 01/30/2017. The I2 index was used to measure heterogeneity between the studies. Results: In a total of 667 documents, 30 (4.49%) were selected. In this study, the prevalence of GBS colonization in 10090 Iranian pregnant women was calculated as 13.65% [confidence interval (CI): 95%: 10.56-17.45]. Based on geographic region,24.63% [CI: 95%: 11.52-45.06] in the West and 8.75% [CI: 95%: 6.43-11.8] in the East were the highest and lowest areas in Iran, respectively, and were statistically significant (p = 0.001). Also, with regards to swapping sampling area, Vaginal with 11.96%, Vaginal and Rectal with 13.62%, and Anal and Vaginal with 25.63% were the least to the greatest, respectively, and were statistically significant (p = 0.001). Conclusion: Therefore, based on the recommendation of Centers for Disease Control and Prevention as reported by the Ministry of Health and Medical education, early diagnosis, and screening of high-risk women should be done at 35-37 weeks of pregnancy.